Corporate social responsibility through SDGs: Preliminary results from a pilot study in Italian universities - Antonio Costa; Alessandra Tafuro; Marco Benvenuto; Carmine Viola (Administrative Sciences, 2021)
Background: In the broad scientific debate on the integration of corporate social responsibility (CSR) in the strategic planning of universities and on the use of monitoring the results of the strategy of the indicators relating to the pursuit of sustainable development goals (SDGs), there is a lack of studies demonstrating the effective degree of institutionalization of CSR in universities. Methods: This analysis constitutes a pilot study relating to the Italian university context. The study was carried out through an analysis on the contents of the three-year strategic performance plans (2020-2022) drawn up by individual universities and compulsorily published on the national portal of the Public Function Department, as required by article 10, paragraph 1, letter (a) of Legislative Decree 150/2009. A matrix was made with the information extracted by the documents and relative to the presence of the SDGs in the strategic performance plan. Consequently, using a Likert scale, the different degrees of institutionalization of CSR in the strategic plan of the universities were coded. Results: The results of the pilot study highlighted that the strategic planning of Italian universities' CSR practices and the challenges of sustainable development are hardly ever systematically addressed. Therefore, there is a low degree of institutionalization of CSR in the Italian university system, even though the literature shows a high cultural and scientific commitment to establish university and post-graduate study courses with corporate social responsibility and sustainable development content and an increasing trend in the use of the accountability tools such as the social report or the sustainability report. Conclusions: It is necessary to share the results of scientific research on CSR and SDGs with the government and governance bodies of universities in order to harmonize the CSR and sustainability culture of these bodies with that of academics.
Keywords: 350; sustainable development; CSR; university; SDGs; institutionalization; performance measurement; strategic plan